La tertulia radiofónica, foro para el siglo XXI - Moreno Espinosa, Pastora (Estudios sobre el Mensaje Periodístico, 2002)
In its origin, the social gathering intimately is bound to the communication in group and a physical space, the coffees. On social gatherings it knows and it must too much Spanish Literature, but today due to the changes of articles of incorporation, the ways and fashions of communication have varied much. The main transmitters of radio of the country, even the premises, have a social gathering space where four or five people related to the world of the policy or the letters talk on present time subjects, sometimes in a friendly way and others with an elevated tone more. These char them, which in Spain always they were bound to the coffees, they appear in the average radius as a sort stars, that has produced authentic rivalries. The radio is therefore the means of the word par excellence, procedure of the faster and immediate communication. And in this sense, it is possible to say that no longer the information in radio without making reference constant to a type can study of space that acquires day-to-day greater force, the social gathering. A space, on the other hand, little treaty by the students of wireless means and whom we approached here. The social gathering has been formed as an authentic forum of debate and opinion that detaches To the reality for its better knowledge and interpretation, key element of this study.
Keywords: Social gathering; conversation; word; forum; public; debate; space; group; policy; communication